TMET-20. TERT ACTS VIA FOXO1 TO ALTER REDOX METABOLISM IN BRAIN TUMORS. (14th November 2022) - Batsios, Georgios; Taglang, Celine; Tran, Meryssa; Gillepspie, Anne Marie; Viswanath, Pavithra
Abstract: Telomere maintenance is a fundamental hallmark of cancer. Most tumors maintain telomere length via reactivation of telomerase reverse transcriptase (TERT) expression. Identifying imaging biomarkers of TERT can enable non-invasive assessment of tumor proliferation and response to therapy. Deuterium magnetic resonance spectroscopy (DMRS) following administration of 2 H-labeled substrates recently emerged as a novel, clinically translatable method of monitoring metabolic activity in vivo . The goal of this study was to delineate metabolic reprogramming associated with TERT expression and to leverage this information for non-invasive imaging of tumor burden and treatment response in gliomas. Our results indicate that TERT expression is associated with elevated levels of the redox metabolite NADH in glioblastomas and oligodendrogliomas. Mechanistically, TERT expression is associated with inhibitory phosphorylation and cytosolic sequestration of FOXO1. FOXO1, in turn, negatively regulates nicotinamide phosphoribosyl transferase (NAMPT), which is the rate-limiting enzyme in NAD+ biosynthesis. As a result, TERT upregulates NAMPT, resulting in elevated steady-state pools of NAD+ and NADH. Concomitantly, FOXO1 negatively regulates the glycolytic enzyme glyceraldehyde-3-phosphate dehydrogenase, which converts NAD+ to NADH. As a result, TERT upregulates the NADH/NAD+ ratio. Since elevated NADH and NADH/NAD+ ratio drive pyruvate conversion to lactate, we then examined whether DMRS-based imaging of [U- 2 H]-pyruvate metabolism reports on TERT expression in gliomas. Our results indicate that doxycycline-inducible TERT silencing significantly reduces lactate production from [U- 2 H]-pyruvate in tumor-bearing mice. Importantly, [U- 2 H]-pyruvate metabolism to lactate differentiates tumor from normal brain in vivo, including at clinical field strength (3T). Furthermore, [U- 2 H]-pyruvate reports on early response to treatment with TERT inhibitors or with radiochemotherapy in mice bearing orthotopic patient-derived gliomas at early timepoints before radiographic alterations can be visualized by magnetic resonance imaging. Collectively, our studies integrate a mechanistic understanding of TERT biology with innovative imaging that has the potential to improve assessment of tumor burden and treatment response for glioma patients.